2022
DOI: 10.23736/s1824-4785.19.03156-x
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG-PET/CT imaging of uterine cervical cancer recurrence in women with and without HIV infection

Abstract: Background: To compare the rate, time and, pattern of recurrence of cervical cancer between patients with and without HIV infection and to determine factors predicting cervical cancer recurrence in patients evaluated by 18 F-FDG-PET/CT. Methods:We reviewed the 18 F-FDG-PET/CT images of patients with histologically proven cervical carcinoma who were presenting with suspected recurrence. We extracted epidemiologic data, previous treatment, histologic subtype, HIV status, viral load and CD4 counts from the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…We found that HIV-infected patients were younger at diagnosis than HIV-uninfected patients, by an average of almost 13 years. This trend seems to be consistent in other squamous cell carcinomas such as cervical and anal cancers 27–30 . The reason for this younger age at diagnosis may be linked to changing trends in the disease; however, a connection with HPV infection still remains the most well-studied implicating factor.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We found that HIV-infected patients were younger at diagnosis than HIV-uninfected patients, by an average of almost 13 years. This trend seems to be consistent in other squamous cell carcinomas such as cervical and anal cancers 27–30 . The reason for this younger age at diagnosis may be linked to changing trends in the disease; however, a connection with HPV infection still remains the most well-studied implicating factor.…”
Section: Discussionsupporting
confidence: 60%
“…This trend seems to be consistent in other squamous cell carcinomas such as cervical and anal cancers. [27][28][29][30] The reason for this younger age at diagnosis may be linked to changing trends in the disease; however, a connection with HPV infection still remains the most well-studied implicating factor. A study by Hampl et al 2 with over 200 women found an increase in the presence of vulva carcinoma in younger patients due to HPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…43 The FDG PET/CT also exhibits good diagnostic performance in endometrial carcinoma 44 and cervical cancer. 45 Numerous studies report on the application of 3D-PDU in various diseases. Data show that the sensitivity of 3D-PDU is higher than that of digital rectal examination, greyscale ultrasonography and power Doppler ultrasonography, but its specificity is lower.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the initial diagnosis of cervical cancer is generally a gynecological examination, which is less reliable in the diagnosis of parauterine infiltration, degree of infiltration, tumor size, and the distant metastases of lymph nodes or pelvic cavity [ 7 ]. At present, clinical imaging methods, such as magnetic resonance imaging (MRI) plain scan, ultrasound, and computer tomography (CT), are used to evaluate the staging of cervical cancer [ 8 , 9 ]. Ultrasound is simple, fast, and easy to operate, with a relatively cheap price.…”
Section: Introductionmentioning
confidence: 99%